Given the system of equations:
y = 3x + 2
y = -2x - 8
Let's solve the system of equations for the values of x and y.
Take the following steps:
Step 1:
Eliminate the equal sides of both equations and combine
3x + 2 = -2x - 8
Let's solve for x.
Step 2:
Subtract 2 from both sides:
3x + 2 - 2 = -2x - 8 - 2
3x = -2x - 10
Step 3:
Add 2x to both sides
3x + 2x = -2x + 2x - 10
5x = -10
Divide both sides by 5:
Step 3:
Substitute -2 for x in either of the equations and solve for y.
Let's take equation 1:
y = 3x + 2
y = 3(-2) + 2
y = -6 + 2
y = -4
Thus, we have;
x = -2, y = -4
In point form, the solution for the system of equations is:
(x, y) ==> (-2, -4)
ANSWER:
a. (-2, -4)